BIOREMEDIATION FORMULA: SPORULATION INDUCTION AND ENDOSPORE STABILITY OF Bacillus pseudomycoides RAY21 IN BIO-OSD - Simatupang, Yeni Veronika; Fauzi, Anas Miftah; Yani, Moh.; Hambali, Erliza (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2025)
Oil-based soil pollution is a pressing global environmental issue and has serious impacts on ecosystems and human health. Hydrocarbon compounds, especially heavy fractions, are persistent and difficult to decompose naturally in a short time, thus requiring intervention to accelerate the environmental recovery process. This research focuses on developing strategies to increase the effectiveness of oil-contaminated soil degradation. The development of a palm oil-based oil spill dispersant (Bio-OSD) combined with bacterial endospores of Bacillus pseudomycoides RAY21 offers an innovative approach to bioremediation. This particular bacterial endospore was selected for its capacity to sustain the viability of a potent biological agent until the point of application. The bacterial growth process was monitored to determine the optimal harvesting time by measuring optical density (OD600) at hourly intervals using a spectrophotometer until the stationary phase was reached. Following the harvesting of bacterial cells, various stressors were applied to stimulate sporulation, which included high-temperature incubation (80°C), nutrient deprivation, and their synergistic combination. The efficacy of the sporulation process was validated through endospore staining with malachite green. The resultant endospore pellets were integrated into the Bio-OSD and subjected to viability assessments every three days over a 24-day period using the Total Plate Count (TPC) method. The biodegradative capacity of the Bio-OSD containing endospores was evaluated through the analysis of Total Petroleum Hydrocarbon (TPH) degradation in artificially contaminated soils (3%) across a 28-day incubation. Findings indicated that optimal bacterial cell production occurred in Nutrient Broth, with peak harvesting at 40 hours. Moreover, the most effective sporulation was attained under combined stress conditions specifically, exposure to high temperature (80 °C for 24 hours) concomitant with nutrient deprivation (NaCl 0,85%) as demonstrated by the presence of green-stained endospores. This study provides evidence that Bio-OSD functions effectively as a stable carrier medium for bacterial endospores over a period of up to 24 days. The Bio-OSD formulation incorporating Bacillus pseudomycoides RAY21 endospores demonstrated the capability to degrade 78% of Total Petroleum Hydrocarbons (TPH) in petroleum-contaminated soil after 28 days of incubation. This degradation efficiency was significantly superior to that of the control treatment, which achieved a mere 32% degradation under the same laboratory conditions. To enhance the understanding and application of this approach, further investigations are recommended to be conducted on a larger scale, along with optimization analyses, to facilitate the development of more sustainable environmental remediation.